Encyclopedia of world cultures - Levinson, David 1947- (G.K. Hall, 1991)
A basic reference source to the cultures of the world. Provides descriptions of all the cultures of each region of the world or of a representative sample of cultures forregions where full coverage is impossible, as well as accurate descriptions of cultures of the past.